2022
DOI: 10.1200/jco.2022.40.16_suppl.2590
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of pembrolizumab for HPV-associated papilloma patients with laryngeal, tracheal, and/or pulmonary involvement.

Abstract: 2590 Background: Recurrent respiratory papillomatosis (RRP) is caused by human papillomavirus (HPV) types 6 & 11. RRP proliferates in the squamous epithelium lining the respiratory tract impacting breathing, swallowing, and voice and carries a 3-5% risk of malignant transformation. Given the multi-focality of the disease and tolerized host immune response against HPV, in part through upregulation of the PD1:PDL1 axis, the safety and efficacy of systemic pembrolizumab (pembro) as a novel treatment for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, disease recurrence can occur when bevacizumab is discontinued, 21,22 suggesting long‐term immunologic control of the disease is needed to provide long‐lasting protection. Two separate studies investigating the use of avelumab or pembrolizumab for the treatment of adult patients with RRP have shown significant reductions in RRP disease burden without surgery, with evaluable HPV‐specific T‐cell responses in several patients; treatment was well tolerated 11,12,14 . Studies on the use of locally injected cidofovir as an adjuvant treatment with surgical debulking of papillomatous disease have shown equivocal results, with clinical benefit not always demonstrated 12 ; moreover, a Cochrane review of the sole prospective clinical study in this regard found no significant difference between cidofovir treatment and placebo at 12 months 23 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, disease recurrence can occur when bevacizumab is discontinued, 21,22 suggesting long‐term immunologic control of the disease is needed to provide long‐lasting protection. Two separate studies investigating the use of avelumab or pembrolizumab for the treatment of adult patients with RRP have shown significant reductions in RRP disease burden without surgery, with evaluable HPV‐specific T‐cell responses in several patients; treatment was well tolerated 11,12,14 . Studies on the use of locally injected cidofovir as an adjuvant treatment with surgical debulking of papillomatous disease have shown equivocal results, with clinical benefit not always demonstrated 12 ; moreover, a Cochrane review of the sole prospective clinical study in this regard found no significant difference between cidofovir treatment and placebo at 12 months 23 …”
Section: Discussionmentioning
confidence: 99%
“…The safety profile and efficacy of INO-3107 plus EP in the present study are in line with other nonsurgical/ adjuvant therapies for RRP, such as bevacizumab and ICIs, and appear to be better than those of the antiviral medication, cidofovir. [11][12][13][14][15] Two recent systematic reviews of bevacizumab for the treatment of severe RRP have shown marked improvements in symptoms with a reduced need for surgical intervention during long-term follow-up (range, 2 months to 5 years), with many patients not requiring any surgery while on treatment. Bevacizumab treatment was safe and well tolerated, with side effects considered as mild or moderate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…45,46 Multiple PD-1 inhibitors such as pembrolizumab and avelumab are involved in clinical trials for treatment of adult RRP. 47,48…”
Section: Pd-1 Inhibitormentioning
confidence: 99%